PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MEMBERIKAN PERLINDUNGAN TERHADAP PENGUNGSI ANAK AFGANISTAN DI KOTA PEKANBARU (INDONESIA) PADA TAHUN 2019-2020 (STUDI KASUS: PENGUNGSI ANAK AFGANISTAN DI RUMAH DETENSI IMIGRASI PEKANBARU) - Jusman Marianto Simanjuntak (UIR Press, 2020)
This study analyzes the role of UNHCR as an international organization that receives a direct mandat from the United Nations to handle problems and provide protection for Afghan child refugees in Pekanbaru-Indonesia in 2019-2020 with a focus on research on Afghan child refugees in the Pekanbaru immigration detention center. The research method is library research and interviews. The framework used by the author is the level of analysis used by international organizations, the theory used by the role theory, the concept of human security and the neoliberal perspective. I can conclude that the international organization in charge of providing protection, namely UNHCR, carries out its duties and roles in providing protection for Afghan child refugees in Pekanbaru City, in a slow way. Where in the refugee child health sector they are able to access public health facilities where Afghan child refugees are located, the refugee education sector has also gained access to general or national education in areas where Afghan child refugees are located, the social service sector for refugee children who have experienced trauma and lost their families. refugees provide livelihood and resilience programs as well as help Afghan child refugees and other child refugees and child refugees are given the freedom to get entertainment at a monthly fee provided by IOM to meet the needs of the refugees.